Molecular Detection of Candida tropicalis Isolated from Immunocompromised Patients with Otitis Media - Aymen Nazar Khalil; Abbas M. Ammari (Academic Science Journal)
Otomycoses are fungal infections that affect the external ear canal and, in some cases with perforated tympanic membranes, the middle ear. Candida are most common fungal genera causative agents of otomycoses. Candida tropicalis is a species of yeast in the genus Candida. One hundred swaps were collected from patients with otitis media who attended ENT consulting clinic at Baquba Teaching Hospital for a period extended from 15th of December 2022 to the 15th of March 2023. The specimens were collected from immunocompromised and immunocompetent patients (50 each of). Clinical diagnosis was done by consultant Otolaryngologist.  Cultural methods including (Sabouraud's dextrose agar medium (SDA) and Hi-Chrom Candida agar) media with incubating at 37°C for 48 h, and Molecular methods (Conventional PCR and gene sequencing) for ITS and Als2 genes were used for identification of C. tropicalis . The susceptibility of isolated C. tropicalis was tested toward fluconazole (10 mg) and miconazole (10 mg) antifungals by using disk diffusion method. The results were males have the highest rate among immunocompromised patients with otitis media (58.0%). According to the rate of C. tropicalis identification, 14.0% (7 out of 50) isolates were collected from otitis media immunocompromised patients. Antibiotic susceptibility results revealed that only 3 isolates of C. tropiclais (25.0%) were resistant against both antibiotics (Fluconazole and Miconazole). PCR results showed that the molecular weight of ITS and als2 genes are was 520 bp and 80 bp., respectively. The mutant isolate, has more than one substitution mutations. We are concluded that Candida tropicalis  is reported as the most causative agent of otitis media. Als2 gene may be play an important role in the virulence of C. tropicalis among immunocompromised patients with otitis media.